2021
DOI: 10.1101/2021.10.22.465448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A poxvirus decapping enzyme localizes to mitochondria to regulate RNA metabolism and translation, and promote viral replication

Abstract: Decapping enzymes remove the five-primer cap of eukaryotic mRNA, leading to accelerated RNA decay. They are critical in regulating RNA homeostasis and play essential roles in many cellular and life processes. They are encoded in many organisms and viruses, including vaccinia virus, which was used as the vaccine to eradicate smallpox. Vaccinia virus encodes two decapping enzymes, D9 and D10, that are necessary for efficient viral replication and pathogenesis. However, the underlying molecular mechanism regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Both the lack of splicing and the presence of a 5' poly(A) tract on late transcripts presumably contribute to the relative protection of viral transcripts against promiscuous decapping. Additionally, a recent study showed that D10 is localized to the mitochondria, which are excluded from the viral factories where viral transcripts are synthesized (30). This observation is also interesting considering our finding that the most downregulated transcripts by D10 included genes involved in oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Both the lack of splicing and the presence of a 5' poly(A) tract on late transcripts presumably contribute to the relative protection of viral transcripts against promiscuous decapping. Additionally, a recent study showed that D10 is localized to the mitochondria, which are excluded from the viral factories where viral transcripts are synthesized (30). This observation is also interesting considering our finding that the most downregulated transcripts by D10 included genes involved in oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 68%
“…Another possibility is that D10 interacts with the spliceosome machinery and is itself co-transcriptionally loaded onto mRNAs. Although D10 is predominantly cytoplasmic, it is present in the nucleus (30), raising the possibility that it could target mRNA in both compartments.…”
Section: Discussionmentioning
confidence: 99%